Програмний модуль «База інженерних знань для структурного синтезу газодувок» - Вершков, Олександр Олександрович; Мацулевич, Олександр Євгенович; Михайленко, Олена Юріївна; Тетервак, Ілля Романович; Verchkov, Oleksandr; Matsulevych, Oleksandr; Mykhailenko, Olena; Tetervak, Illia (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: Виробничі підприємства дуже залежать від цін на продукцію, на робочу силу та на нові програмні продукти, які можуть значно скоротити витрати. Наявна на сьогодні проблема впливає на збільшення часу на розробку чи конструювання нових приладів, тим самим зменшуючи ефективність праці. Наслідком цього є великі витрати, які не виправдовують очікування. Проаналізувавши комерційні програмні продукти, ми дійшли висновку, що вони є висококласними, але дуже дорогими, для їх використання треба придбати ліцензію, для впровадження – мати потужне програмне забезпечення, а для чіткого функціонування будь- якої із систем потрібна штатна група ІТ-спеціалістів високого рівня. Наводиться інтерфейс усіх форм модуля розрахунку собівартості, додано зв’язок із регістрами та рахунками бази знань, а також розроблено і проведено тестування додатка. Проведено верифікацію додатка. Виявлено, що створена інформаційна система повністю відповідає технічному завданню і не має логічних помилок. /// EN: In the age of information technology, the ability to work with large amounts of data is critically important, and knowledge bases are actively used for this purpose. Long-term storage and processing of information is an integral part of the functioning of almost all modern systems. Thus, information is a key resource for ensuring efficiency in any industry. Due to the growth of data flows and the need for faster processing, automation is necessary: manual operations are becoming inefficient. The quality of administrative decisions now depends on the most accurate and reliable assessment of current dynamics and potential prospects. The behavior and motivation of the developers are quite understandable and justified. The task is set – to develop a knowledge base for the structural synthesis of gas blowers in the enterprise’s design documentation system. One of the popular multi-user SKBZs and tools for quick calculation of gas blowers is selected. Finally, the system itself is created, which is a combination of a knowledge base and applications that refer to it. After analyzing commercial software products and concluding that they are high-end and therefore very expensive, a license must be purchased for use, high-end software is required to implement these products, and a staff of high-level IT specialists is required for the smooth operation of any of the systems. The paper presents a new software module. It provides an interface for all forms of the cost calculation module, adds links to registers and knowledge base accounts, and develops and tests the application. The application has been verified. It has been found that the created information system fully complies with the technical specifications and has no logical errors.
Software module “Engineering knowledge base for structural synthesis of gas pipes"
Keywords: програмний модуль; база інженерних знань; газодувка; компресор; структурний синтез; собівартість; валідація; верифікація; software module; engineering knowledge base; gas blower; compressor; structural synthesis; cost; validation; verification